Gadofosveset-enhanced lung magnetic resonance imaging to detect ongoing vascular leak in pulmonary fibrosis. Issue 5 (17th May 2018) - Montesi, Sydney B.; Rao, Rohan; Liang, Lloyd L.; Goulart, Hannah E.; Sharma, Amita; Digumarthy, Subba R.; Shea, Barry S.; Seethamraju, Ravi T.; Caravan, Peter; Tager, Andrew M.
Vascular leak is a cardinal response to tissue injury [1, 2]. When dysregulated, vascular leak has been shown to contribute to the development of pulmonary fibrosis in the bleomycin mouse model [3]. Specifically targeting vascular endothelial growth factor, initially described as vascular permeability factor [4] and a key mediator regulating capillary permeability, attenuates the development of pulmonary fibrosis in vivo [5]. Gadofosveset (Ablavar; Lantheus Medical Imaging Inc., North Billerica, MA, USA) is a US Food and Drug Administration-approved, gadolinium-based, albumin-binding contrast agent. Gadofosveset has been used to detect vascular permeability in mouse models [6] and to perform vascular imaging clinically. We hypothesised that gadofosveset-enhanced lung magnetic resonance imaging (MRI) could detect albumin extravasation in subjects with pulmonary fibrosis and demonstrate the location of ongoing tissue injury. Vascular leak is increased diffusely in the lungs in pulmonary fibrosis and is not limited to radiographic areas of disease involvement http://ow.ly/Zz6Z30jb85l